Uji Daya Hasil Varietas Lokal Tembakau Bondowoso - Yulaikah, Sri; Amir, Andi Muhammad (Universitas Muhammadiyah Yogyakarta, 2016)
Bondowoso tobacco is a type of Â sliced tobacco that is developed in eleven district i.e. Bondowoso, Tenggarang, Tegal Ampel, Pakem, Curahdami, Maesan, Pujer, Wonosari, Binakal, Taman Krocok and Wringin. In order to fulfill the improvement of new variety program, yield evaluations is a step that should be done. The aims of the experiment were to examine the yield of local varieties, the superior traits and then choose the best variety. The experiment was conducted on March to September 2009 in tobacco producing areas. The experiment tested 6 local Â varieties i.e. Sam1, Se2, Mar3, Sam4, Sam5 and Sam6. Each of them was plant with three replicates. The experiment design was Â randomized complete block design (RCBD). Each plot consisted of 200 plants. The result showed that three varieties of which relatively had the same superiority on characters: yield potensial, quality index, plant index, nicotine content and disease tolerance. The selected varieties were Sam1, Sam5 dan Sam6, with yield potensial each acession i.e: 1.682 kg/ha, 1.399 kg/ha and 1.282 kg/ ha.